Лабиринты западноевропейской русистики - Figarski, Władysław (Wydawnictwo Naukowe UAM, 2013)
The article focuses on the complex process of development and the actual state of contemporary Russian studies in selected countries of Western Europe. The author describes this hard and thorny path of development which, like a maze, is intricate and ambiguous as well as full of difficulties and obstacles, and he analyzes the condition of Russian studies in England, France, Italy and Spain.
Labyrinths of Russian studies in Western Europe
O niektórych meandrach w rusycystyce zachodnioeuropejskiej